Surgical complications of vagus nerve stimulation surgery: A 14-years single-center experience - Jouke van Schooten; Jacco Smeets; Sander MJ. van Kuijk; Sylvia Klinkenberg; Olaf E.M.G. Schijns; Jeske Nelissen; Louis G.L. Wagner; Rob P.W. Rouhl; Marian H.J.M. Majoie; Kim Rijkers (Brain and Spine)
Introduction: Vagus nerve stimulation (VNS) is the most frequently used neuromodulation treatment for Drug-Resistant Epilepsy (DRE) patients. Complications of VNS surgery include surgical site infection and unilateral vocal cord paresis. Complication rates vary across studies. Research question: What is the safety profile of VNS related surgeries? Materials and methods: Retrospective cohort study using patient files of DRE-patients who had undergone primary implantation of a VNS-system, replacement of the VNS pulse generator, replacement of the lead, replacement of both pulse generator and lead, or VNS removal surgery in the Maastricht UMC+. Multiple Imputation was used for missing data. Univariable and multivariable logistic regression analysis were performed to analyze possible risk factors, in case of a small sample size, an independent-samples t-test and Fisher's exact test or Pearson's X2-test were used. The complication rate was calculated as percentage. Results: This study included a total of 606 VNS surgical procedures, leading to 67 complications of which 3 permanent complications. Complication rate after primary implantation was 13.4%; 2,5% for pulse generator replacement; 21.4% for lead revision and 27.3% for complete VNS removal. No statistically significant results were found when analyzing the results of adults and children <18 years separately. Discussion and conclusion: Complication rates of VNS-related surgeries in our own institutional series are low and comparable to previously reported series. VNS surgery is a relatively safe procedure. The complication rate differs per type of surgery and mean surgery duration was longer for patients with complications after lead revision surgery compared to patients without complications.